Kidney, Pancreas and Liver Allocation and Distribution in the United States - Smith, J. M. (2012)
Kidney transplant and liver transplant are the treatments of choice for patients with end-stage renal disease and end-stage liver disease, respectively. Pancreas transplant is most commonly performed along with kidney transplant in diabetic end-stage renal disease patients. Despite a steady increase in the numbers of kidney and liver transplants performed each year in the United States, a significant shortage of kidneys and livers available for transplant remains. Organ allocation is the process the Organ Procurement and Transplantation Network (OPTN) uses to determine which candidates are offered which deceased donor organs. OPTN is charged with ensuring the effectiveness, efficiency and equity of organ sharing in the national system of organ allocation. The policy has changed incrementally over time in efforts to optimize allocation to meet these often competing goals. This review describes the history, current status and future direction of policies regarding the allocation of abdominal organs for transplant, namely the kidney, liver and pancreas, in the United States.